4D printed thermochromic Fresnel lenses for sensing applications. (1st February 2022) - Ali, Murad; Alam, Fahad; Fah, Yap Fook; Shiryayev, Oleg; Vahdati, Nader; Butt, Haider
Abstract: The conventional manufacturing processes for optical sensors fabrication have limitations in terms of ease of fabrication, design freedom, mechanical flexibility, cost requirements, etc. Therefore, adapting additive manufacturing (3D printing) is highly desirable because it opens up a variety of design and manufacturing possibilities. We have demonstrated that the 3D fabrication process using computer-aided design may be used to fabricate 4D functionalized photonic devices such as Fresnel lenses. We have introduced spectral color variation as the fourth dimension to 3D printed lenses in response to temperature as an external stimulus. The digital light processing (DLP) 3D printing process parameters were optimized to print the needed features with precise geometric dimensions of the lenses. Thermochromic pigment powders were mixed in the liquid monomer resins to print tinted Fresnel lenses used for selective color focusing and temperature sensing applications. The focusing ability and thermal sensing of printed lenses were assessed using customized setups that included normalized power intensity and transmission spectra measurements. Contact angle measurements were used to determine surface wettability, revealing the hydrophilic nature of the lens material. 3D printing offers custom-built optical devices and the ability to optimize the materials for both active and passive optical sensing applications, making them more promising than traditional Fresnel lenses.